By His Excellency the Honourable George Clinton, captain general and governor in chief of the province of New-York ... A proclamation : Whereas several incroachments have lately been made by the inhabitants of the provinces of Massachusetts-Bay and New-Hampshire, upon the lands and possessions of divers of His Majesty's subjects, holding the same by virtue of letters patents under the great seal of this province ... Given under my hand and seal at arms at Fort-George, in the city of New-York, the twenty eighth day of July, in the year of our Lord one thousand seven hundred and fifty three . ([Printed by James Parker], 1753)
Authorizing the apprehension of persons from Massachusetts or New Hampshire laying claim to New York lands.